Quasi‐Ionic Liquid Enabling Single‐Phase Poly(vinylidene fluoride)‐Based Polymer Electrolytes for Solid‐State LiNi0.6Co0.2Mn0.2O2||Li Batteries with Rigid‐Flexible Coupling Interphase. Issue 7 (21st May 2021) - Xu, Fanglin; Deng, Shungui; Guo, Qingya; Zhou, Dong; Yao, Xiayin
Abstract: Poly(vinylidene fluoride)‐based polymer electrolytes are being intensely investigated for solid‐state lithium metal batteries. However, phase separation and porous structures are still pronounced issues in traditional preparing procedure. Herein, a bottom‐to‐up strategy is employed to design single‐phase and densified polymer electrolytes via incorporating quasi‐ionic liquid with poly(vinylidene fluoride‐ co ‐hexafluoropropylene). Due to strong ion/dipole–dipole interaction, the optimized polymer electrolyte delivers high room‐temperature ionic conductivity of 1.55 × 10 −3 S cm −1, superior thermal and oxidation stability of 4.97 V, excellent stretchability of over 1500% and toughness of 43 MJ cm −3 as well as desirable self‐extinguishing ability. Furthermore, the superb compatibility toward Li anode enables over 3000 h cycling of Li plating/stripping and ≈98% Coulombic efficiency in Li||Cu test at 0.1 mA cm −2 . In particular, lithium metal battery Li||LiNi0.6 Co0.2 Mn0.2 O2 exhibits a room‐temperature discharge retention rate of 96% after 500 cycles under a rate of 0.1 C, which is associated with the rigid‐flexible coupling electrodes/electrolytes interphase. This investigation demonstrates the potential application of quasi‐ionic liquid/polymer electrolytes in safe lithium metal batteries. Abstract : Quasi‐ionic liquid Li(DMF)3 TFSI enables single‐phase poly(vinylidene fluoride‐ co ‐hexafluoropropylene) (PVDF‐HFP) polymer electrolytes with high strength and toughness, which facilitate uniform Li deposition through homogeneous Li + flux and contact pressure. Meanwhile, PVDF‐HFP segments are involved in the interfacial chemistry to form robust polymeric solid electrolyte interphase, induced by strong intermolecular interactions between Li(DMF)3 TFSI and PVDF‐HFP.